(3efGgL GdeMOKjf aj fbO GdQhGjGJ GdJGQjNjI ddbQhf GdgLQjI GdKdGKI GdChdi (B/s - (3GdTgQRhQj, EHQGgje Cejf GdLGas ((3OHj, GdEeGQGJ GdYQHjI GdeJMOI (B:s (3OGQ Gdbde,s, 2014)
(3cJGH efGgL GdeMOKjf aj fbO GdQhGjGJ GdJGQjNjI ddbQhf GdgLQjI GdKdGKI GdChdi ddcGJH EHQGgje Cejf GdLGa GdTgQRhQj GdHZOGOj gh cJGH jJMOK Yf GdJOhjf GdJGQjNj YfO GdeSdejf hYf efgL GdMOjK GdfHhj GdTQja cPdc PcQ GdeDda GdeJf YfO GdeDQNjf heYfGg hSeGJg hefGgL GdCUhdjjf ef YdeGA CUhd Gdabg hefGgL GdCFeI GdabgGA GdcHGQ dgPg GdCeI hjJeJY GdcJGH HcKGaI GdeYdheGJ GdJGQjNjI hGdOjfjI aj Bf hGMO(B.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
(3jJhGaQ HGdecJHI (B: (3eLdO (B1 (3,(B2.s
Keywords: (3Yde QhGjI GdMOjKs; (3GdMOjKs -- (3ESfGOs